The use and efficacy of the offensive action of pick and roll in the Olympic Games of 2020 - Bismpos, M.; Karamousalidis, G. (Journal of Physical Education and Sport, 2022)
The following research was conducted with the purpose of investigating and ascertaining the efficacy of Pick and Roll, depending on how they are dealt with by each defense, and to which extent they affect the outcome of a game on the highest worldwide level. For the actualization of this purpose, 26 games from the Olympic Men`s Basketball Tournament of 2020 were analyzed. The survey`s sample consisted of the 12 teams that took part in the Tournament. Of these 26 games, 798 Pick and Roll, from which the data was acquired, were recorded and analyzed. For the record and the analysis of the games the notational analysis program InstatScout-Basketball was used. In order to ascertain the frequencies of the defined variables and the differences between them, crosstabulation analysis with x^2 (Chi-square) distribution was performed and the level of significance was set at p<0.05. The results showed that the efficacy of Pick and Roll statistically affects the outcome of a game (x^2=9.7, p=0.002). The Center was the most efficient in the execution after the Pick and Roll (x^2=26.6, p=0.001). The most efficient ending of the Pick and Roll was "pass to roll" (x^2=40.8, p=0.001). The "over" was the most efficient reaction to the Pick and Roll (x^2=18.6, p=0.002). Finally, from the present research was shown that the winning teams execute more successful Pick and Roll and fewer unsuccessful one, while the losing teams the opposite (x^2=9.7, p=0.002). The data and the information that came up from this survey can help the coaching staffs, so that they can be prepared appropriately and use the Pick and Roll with more efficiency.